Analysis of Causative Microorganism in 248 Primary Hip Arthroplasties Revised for Infection: A Study Using the NJR Dataset. Issue 1 (January 2016) - Holleyman, Richard J.; Baker, Paul N.; Charlett, Andre; Gould, Kate; Deehan, David J.
Introduction: This study aimed to describe the epidemiology of the causative organism in a series of primary hip arthroplasties revised for a diagnosis of periprosthetic joint infection (PJI) in England and Wales. Methods: Patient data from the National Joint Registry (NJR) was linked to microbiology data held by Public Health England (PHE) which identified a series of 248 primary hip arthroplasties revised for PJI between 2003 and 2014. Definitive cultures, isolated at time of revision surgery, were available for all cases. Total hip arthroplasty (n = 239, 96%) and hip resurfacing (n = 5, 2%) were the most commonly performed primary procedures. A two-stage revision was the most common operative management (n = 174, 70%). Results: 202 (81%) cases were infected with a single genus microorganism and the most commonly implicated genus was Staphylococcus species (70% of all single genus infections). Staphylococcus species were also the most commonly identified microorganism in mixed genus infections (74% of patient's cultures). There was a significant difference in microorganism distribution when comparing uncemented vs cement implant fixation, with a higher incidence of Gram-negative infection observed in the uncemented group (p = 0.048, Chi-square). Conclusions: Both prophylactic and therapeutic antibiotic regimes should be focused on targeting Staphylococci.